Remembering those who were banned - Ensor, Paula (New Agenda: SA Journal of Social and Economic Policy, 2026)
It is estimated that 1,400 South African were banned between the 1951 imposition of the Suppression of Communism Act and 1985 when the last person was banned. The true numbers will never be known; records were only kept from 1958, and the decline in the number of bannings under the Act from the middle of the turbulent 1980s indicated the deployment of more effective weapons of oppression under state of emergency regulations. PAULA ENSOR introduces a remarkable on-line archive of interviews, transcripts and videos of a special group of people who were determined to oppose apartheid, and suffered a heinous assault from the state in response.